Indian Political Thought - O.P. Gauba (New Delhi, 2024)
O.P. Gauba's Indian Political Thought attempts to examine the major concepts and the prominent vocabulary of the ancient as well as modern Indian political thought in a critical and comparative perspective.Under ancient Indian thought, it inquires into the nature of Dharmashastra, Arthashastra, and Buddhist traditions with special reference to the views of Manu, Mahabharata, Kautilya, and the Buddhist philosophy. Then under modem Indian thought, it proceeds to identify the various streams of political thought. Each stream of thought is introduced with the theoretical issues involved in its approach, and the contribution of partici la thinkers thereto. It particularly focuses on the liberal stream, the idealist stream, the humanist stream, exponents of the Islamic thought, the socialist stream, the feminist stream and the critics of the caste system.
English
Keywords: Indian Political Thought; Political Science; Political thought